Flow and heat transfer characteristics of a swirling impinging jet issuing from a threaded nozzle. (June 2021) - Xu, Liang; Yang, Tao; Sun, Yanhua; Xi, Lei; Gao, Jianmin; Li, Yunlong; Li, Jibao
Abstract: A new swirler to excite the swirling jet is proposed to achieve the uniform and efficient impingement cooling, that is, the inner wall of a circular hole is provided with four spiral grooves similar to the conventional circular hole with internal threads. An experimental system is established to study the heat transfer and flow characteristics of the impingement surface. Experiments using smoke flow visualization technology are carried out at Reynolds number ( Re ) of 6000 in free space with/without impingement target respectively to investigate the complex flow field of swirling impinging jets (SIJ), and the effects of jet airflow diffusion and swirl angle on the airflow diffusion are analyzed. Heat transfer experiments are carried out for the swirl angle varying from 0° to 45° at Re varying from 6000 to 30000 for the jet spacing to the nozzle hydraulic diameter ( H/d j ) varying from 1 to 8. The impingement heat transfer rate of the target surface is found to increase slightly with the increase of the swirl angle. Compared with the conventional round hole and the non-swirling impinging jet (the nozzle with the angle of 0°), the swirling jet impingement with a certain swirl angle can effectively improve the overall heat transfer rate of the target surface. At H/d j =2 and H/d j =4, the local Nusselt number ( Nu ) at the stagnation point of the SIJ with the swirl angle of 45° is 7.4% and 11.4% higher than those of conventional round hole jet, respectively. Local Nu on the target surface has a nonlinear proportional relationship with Re, and the maximum Nu is obtained at the location of r/d j =0.7 at a higher Re . With the increase of H/d j, the effect of the swirling flow on impingement heat transfer weakens, and even disappears. An averaged Nusselt number correlation is presented over 6000 ≤ R e ≤ 30000 ， 0 ° ≤ θ ≤ 45 °, and 1 ≤ H / d j ≤ 8, which matches the experimental results very well.